Incidence of mycotoxins in poultry feeds and feed ingredients used in Warangal (TS), India - Parvathi D; Rajender Reddy; Krishna Reddy V (International Journal of Life Sciences, 2017)
Incidence of mycotoxins is a major problem encountered by poultry industry as in most cases low grade feed ingredients are used in the formulation of feeds. Investigations carried out to assess the incidence of mycotoxins in poultry feeds revealed that aflatoxin followed by ochratoxin A were most common and contaminated large number of poultry feeds and feed ingredients. Most of the samples were found to be contaminated with more than one mycotoxin. Farm mixed feed samples were recorded with highest frequencies of mycotoxin contamination than the commercial brands,